SAT0076 EARLY REMISSION IS ESSENTIAL TO PREDICT LONGTERM REMISSION. CLINICAL RESULTS OF THE BELGIAN CAP48 RA COHORT. (June 2019) - Sokolova, Tatiana; Avramovska, Aleksandra; Sidiras, Pascalis; Kleimberg, Sandra; Dierckx, Stephanie; Bellefon, Laurent Meric de; Schreiber, Serge; Ribbens, Clio; Malaise, Michel; Stoenoiu, Maria; Romana, Silvana DI; Badot, Valérie; et al.
Abstract : Background: Early therapeutic intervention is crucial for patients with early rheumatoid arthritis (ERA). The goal of remission is achievable in a proportion of ERA patients. Objectives: To evaluate the rate of patients in remission at 6 months and to correlate the 3 year remission rate. To identify baseline characteristics differences between patients achieving remission or not, and to report the best remission composite criteria to be used in daily care. Methods: The Belgian CAP48 cohort supported by the French speaking radiotelevision (RTBF) is a unique prospective observational study of patients less than 50 years old with a recent diagnosis of ERA. All patients are naïve to DMARDs therapy and were recruited in different rheumatologic centers in Brussels and Wallonia. At baseline and every 6 months, demographic, specific clinical evaluation, questionnaires and laboratory were completed and treatment was adapted according each physician decision. Results: 207 RA patients from 16 centers were analysed (162 F, 45 M, mean age 36.0 years, 27.8% with baseline erosion, 62.3% with ACPA, 59.9% with FR, mean HAQ 1.9, mean DAS28-CRP 4.54, mean SDAI 24.9 and mean CDAI 23.4) history) and a group of 106 patients followed up to 36 months. Clinical results are summarized in this Table. Correlation between early 6 months response and long-term remission at 36 moths was performed in 106 patients: 63 patients achieved DAS28-CRP remission at 36 months versus 43 patients. DAS28-CRP and SDAI composite remission criteria observed at 6 months could predict long-term remission observed at 36 months (Figure); with DAS28-CRP, SDAI and CDAI mean values statistically different (p < 0.01, test-t) between two group. At baseline, the following parameters are similar in two groups "long term remission" and "no long term remission", respectively: age (34.3 vs 33.8 yrs); Female (76.2 vs 72.1%); smoker (24.1 vs 34.2%); ACPA positive (66.7 vs 62.8%); mean DAS28-CRP (4.4 vs 4.7); mean HAQ (1.0 vs 1.2); baseline X-ray erosion (21.7 vs 39.5%). The time for diagnosis and treatment initiation is statistically shorter in "long term remission" group compared to the "no remission group" (mean of 1.4 months vs 3.4 months; p=0.042). Additionally, global remission (DAS28-CRP<2, 6, HAQ<0, 5 and no X-ray progression) was observed in 41.5% of the long term remission group. The majority of these patients (79%) are treated with Methotrexate. Conclusion: Early and long term remission is an achievable goal in our observational CAP 48 study cohort. Early diagnosis is critical in standard of care. At 6 months, DAS28-CRP and SDAI were the best remission criteria to predict long term remission. Acknowledgement: We are grateful to all participating investigators and clinical staffs which have made crucial contributions to the development of this Project. Disclosure of Interests: Tatiana Sokolova: None declared, Aleksandra Avramovska: None declared, Pascalis Sidiras: None declared, Sandra Kleimberg: None declared, Stephanie Dierckx: None declared, Laurent Meric de Bellefon: None declared, Serge Schreiber: None declared, Clio Ribbens: None declared, Michel Malaise: None declared, Maria Stoenoiu Grant/research support from: Abbvie, Roche, Wyeth, Silvana Di Romana: None declared, Valérie Badot: None declared, Patrick Durez Speakers bureau: Bristol-Myers Squibb, Eli Lilly, Sanofi, Celltrion